Application direction of amorphous and nanocrystalline alloy materials and the evaluation of venture capital value. Issue 1 (10th September 2021) - He, Han; Yuan, Xinjian; Liu, Weiwei
Abstract: At present, the country vigorously calls for the use of green, energy-saving and environmentally friendly materials in various fields, especially in electronic power systems that require the use of low-loss soft magnetic alloy materials. Amorphous nanocrystalline alloy materials that have received widespread attention have excellent high magnetic permeability and low loss performance. Therefore, this material has become a power system with energy saving, environmental protection and excellent efficiency. Among them, soft magnetic alloys have the most application prospects. In this paper, various amorphous/nanocrystalline samples have been successfully prepared by vacuum arc melting and rapid cooling. Using XRD, HV and SEM testing and analysis methods, the structure, hardness, mechanical properties, magnetic properties and other alloys were successfully prepared. Mo element improves the ability to form glass from amorphous nanocrystalline alloys, the alloy with alloy composition ( F e 0.5 C o 0.5 ) 66 N b 6 B 26 M o 2 has the best glass forming ability. The addition of Mo deteriorates the soft magnetic properties of the alloy. The saturation magnetic flux density Ms of the alloy is reduced from 81 to 59 emu/g, but the coercive force is not significantly improved. By increasing the Fe content, the amorphous forming ability and heat the stability decreases, the Vickers hardness and corrosion resistance decrease, and the saturation magnetization and coercivity increase. It can reduce the cost of the alloy and improve the magnetic properties of the alloy.